Teacher Challenges In Implementing School/Madrasah Management Standards - Badriah, Eneng Huzaematul; Novitasari; Rochman, Chaerul (Yayasan Mentari Madani, 2023)
The purpose of this research is to explain the teacher's ability to understand and implement the 2020 IASP in the Elementary/Madrasah Management component, as well as to analyze what problems lie behind the teacher's inability to implement it. The method used is descriptive analytical method, with data collection techniques using a questionnaire distributed via Google Form to elementary school teachers and Islamic elementary school teachers in Indonesia. Respondents consisted of 30 teachers who were grouped into 15 PAI teachers and 15 non-PAI teachers. The results of this study found that the ability of PAI and non-PAI teachers to understand and implement IASP 2020 can be seen from the lowest percentage achievement profile, namely 78.3% for PAI teachers, and 68.3% for the non-PAI teacher group. The teacher's problems in implementing IASP 2020 are: First, the level of understanding of the curriculum. Second, the level of understanding of school/madrasah income and expenditure budget planning. Third, the lack of socialization of policies in schools